2014
DOI: 10.1590/0074-0276130601
|View full text |Cite
|
Sign up to set email alerts
|

The mazEF toxin-antitoxin system as a novel antibacterial target in Acinetobacter baumannii

Abstract: Although analysis of toxin-antitoxin (TA) systems can be instructive, to date, there is no information on the prevalence and identity of TA systems based on a large panel of Acinetobacter baumannii clinical isolates. The aim of the current study was to screen for functional TA systems among clinical isolates of A. baumannii and to identify the systems’ locations. For this purpose, we screened 85 A. baumannii isolates collected from different clinical sources for the presence of the mazEF, relBE and higBA TA ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
0
20
1
Order By: Relevance
“…The HigBA and SplTA TA systems were particularly common (88.6% predominance, taking into account the 476 clinical samples). Remarkably, in 46 of the A. baumannii isolates analyzed, expression of the HigBA toxin-antitoxin system was not observed (399,400). All of these toxin-antitoxin systems were found in most clinical isolates of A. baumannii belonging to the ECI and ECII groups worldwide.…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 94%
“…The HigBA and SplTA TA systems were particularly common (88.6% predominance, taking into account the 476 clinical samples). Remarkably, in 46 of the A. baumannii isolates analyzed, expression of the HigBA toxin-antitoxin system was not observed (399,400). All of these toxin-antitoxin systems were found in most clinical isolates of A. baumannii belonging to the ECI and ECII groups worldwide.…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 94%
“…Firstly, the target should be prevalent in the subjected population. So, the bioinformatics analysis helps to find the prevalent target genes and it could have confirmed by experimental analysis (7). Therefore, this type of analysis is cost and time effective in the laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Because of attractive data in genomic databases, it is suggested the bacteria firstly go under the bioinformatics analysis to gain the accurate data (6). Toxin antitoxin (TA) systems in bacteria are currently attractive antimicrobial target (7). There are six different types and mostly are known as a regulon of virulence and alternatively antimicrobial resistant genes (8).…”
Section: Introductionmentioning
confidence: 99%
“…The most common type II TA system in bacteria is mazEF [12][13][14], relEB [15], mqsRA [16]. Several studies suggested the role of TA systems in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%